A molten salt strategy for deriving a porous Si@C nano-composite from Si-rich biomass for high-performance Li-ion batteries. Issue 83 (22nd August 2016) - Lin, Ning; Xu, Tianjun; Han, Ying; Shen, Kangze; Zhu, Yongchun; Qian, Yitai
Abstract : A porous Si@C nano-composite is prepared through deriving both Si and C from biomass for high-performance Li-ion batteries. Abstract : The preparation of a porous Si@C nano-composite from Si-rich biomass such as bamboo leaves is realized through baking the precursor at 400 °C in air, followed by reduction in molten AlCl3 at 200 °C. During this process, both Si and C components in those natural precursors are recovered as active materials. The obtained crystallized Si nanoparticles are embedded well in the pyrolyzed porous carbon matrix. As an anode for Li-ion batteries, the Si@C nano-composite exhibits long-term cycling stability with a capacity of 600 mA h g −1 at 2.0 A g −1 after 3700 cycles.